Options to Use Existing International Offset Programs in a Domestic Context - Partnership for Market Readiness (World Bank, Washington, DC, 2015)
Over the past 25 years significant experience on offsetting has been built up through the development, implementation and improvement of various international and domestic offset programs. A wide range of approaches adapted to different circumstances have been explored. Currently a number of countries are considering the design of their own domestic offset programs. This report will explore different options for drawing on this international knowledge and infrastructure. Leveraging the existing international offset programs can be a way to cost effectively fast start a domestic offset program. Making use of the existing international experience can take the form of different levels of dependencies, ranging from full reliance on international programs on the one hand to a fully independent domestic program in the other extreme case, and everything in between.